Effect of Set-Structure on Upper-Body Muscular Hypertrophy and Performance in Recreationally-Trained Male and Female. Issue 8 (27th August 2022) - Davies, Timothy B.; Halaki, Mark; Orr, Rhonda; Mitchell, Lachlan; Helms, Eric R.; Clarke, Jillian; Hackett, Daniel A.
Abstract: Davies, TB, Halaki, M, Orr, R, Mitchell, L, Helms, ER, Clarke, J, and Hackett, DA. Effect of set structure on upper-body muscular hypertrophy and performance in recreationally trained men and women. J Strength Cond Res 36(8): 2176–2185, 2022—This study explored the effect of volume-equated traditional-set and cluster-set structures on muscular hypertrophy and performance after high-load resistance training manipulating the bench press exercise. Twenty-one recreationally trained subjects (12 men and 9 women) performed a 3-week familiarization phase and were then randomized into one of two 8-week upper-body and lower-body split programs occurring over 3 and then progressing to 4 sessions per week. Subjects performed 4 sets of 5 repetitions at 85% one repetition maximum (1RM) using a traditional-set structure (TRAD, n = 10), which involved 5 minutes of interset rest only, or a cluster-set structure, which included 30-second inter-repetition rest and 3 minutes of interset rest (CLUS, n = 11). A 1RM bench press, repetitions to failure at 70% 1RM, regional muscle thickness, and dual-energy x-ray absorptiometry were used to estimate changes in muscular strength, local muscular endurance, regional muscular hypertrophy, and body composition, respectively. Velocity loss was assessed using a linear position transducer at the intervention midpoint. TRAD demonstrated a significantly greater velocity loss magnitude ( g = 1.50) and muscle thickness of the proximal pectoralis major ( g = −0.34) compared with CLUS. There were no significant differences between groups for the remaining outcomes, although a small effect size favoring TRAD was observed for the middle region of the pectoralis major ( g = −0.25). It seems that the greater velocity losses during sets observed in traditional-set compared with cluster-set structures may promote superior muscular hypertrophy within specific regions of the pectoralis major in recreationally trained subjects.